Unit trust in Malaysia : a study on the relationship between unit trust performance and the fund characteristics / Muhammad Khairul 'Ariffin Azhari - Azhari, Muhammad Khairul 'Ariffin (2018)
Mutual fund is an investment tool that helps investor to increase their wealth while spreading their investment portfolio. In Malaysia, mutual fund is better known as unit dust. This sector has been one of the fastest growing sectors within two decades. With the development of unit trust, Unit Trust Management Company (UTMC) provides a variety of option for investors to pick in order to invest in unit trust. Such enjoyment such as low investment risk due to the diversification of unit trust, affordability and professional fund management can be obtain when one is investing in unit trust. This research will obtain the relationship between unit trust and fund characteristic such as fund age, total return, fund size, management fee and sales charge. The research is a balanced panel data type of research. The observation ranges from the year 2013 until 2017, with a total of 10 unit trust fund. The number of observation is approximately 50. All the data that is used are obtained via the internet. Several test such as regression analysis have been implemented in this research to determine the significant of the data. The outcome of the study are all of the variables are positive relationship except for sales charges.